Status Permudaan Alami Hutan Mangrove di Teluk Buo Bungus Kota Padang - Nadila Safitri; Irma Leilani Eka Putri; Vauzia; Filza Yulina Ade (Jurnal Biogenerasi, 2026)
Mangrove forests are important coastal ecosystems that function as shoreline protectors, carbon sinks, and habitats for many aquatic organisms. In Teluk Buo, Bungus, Padang City, mangrove stands have experienced pressure from land conversion and human activities, so information on natural regeneration is needed to support management efforts. This study aimed to determine the natural regeneration status of mangroves in Teluk Buo based on species density values. The study used a descriptive quantitative method with a plot sampling approach at three observation stations, each consisting of three plots selected by purposive sampling. Observation plots of 10 x 10 m were used for trees, 5 x 5 m for saplings, and 2 x 2 m for seedlings. Data were analyzed using species density and regeneration status criteria according to Shankar (2001). The results showed that two mangrove species were found, namely Rhizophora apiculata and Bruguiera gymnorrhiza. Station 1 had a seedling density of 75, sapling density of 12, and tree density of 26.33, indicating a sufficient regeneration status. Station 2 had a seedling density of 144, sapling density of 24, and tree density of 5.67, while Station 3 had a seedling density of 122, sapling density of 17.33, and tree density of 8.33; both stations indicated good regeneration status. Rhizophora apiculata was the dominant species at all growth levels, whereas Bruguiera gymnorrhiza showed limited regeneration. In general, natural regeneration of mangroves in Teluk Buo was classified as good to sufficient, with regeneration being more strongly supported by Rhizophora apiculata.